Metal Dicyanamides as Efficient and Robust Water‐Oxidation Catalysts. Issue 2 (1st December 2016) - Nune, Satya Vijaya Kumar; Basaran, Aysun Tekin; Ülker, Emine; Mishra, Rupali; Karadas, Ferdi
Abstract: Non‐oxide cobalt‐based water‐oxidation electrocatalysts have received attention recently for their relative ease of preparation, they are stable both in acidic and basic media, and they have higher turnover frequencies than cobalt oxides. Recent studies show that one of the main bottlenecks in the implementation of non‐oxide systems to water splitting is the low number of active metal sites, which is in the order of nmol cm −2 . Herein, a new series of non‐oxide water‐oxidation catalysts has been introduced to the field. Cobalt dicyanamides are observed to have around four times higher surface active sites and better catalytic performances than cyanide‐based systems. Long‐term catalytic studies (70 h) at an applied potential of 1.2 V and electrochemical studies performed in solutions in pH values of 3.0–12.0 indicate that the compounds are robust and retain their structures even under harsh conditions. Moreover, the addition of Ni impurities to cobalt dicyanamides is a feasible method to improve their catalytic activities. Abstract : Water to fuel : New non‐oxide water oxidation catalysts, metal dicyanamides, are investigated as water‐oxidation catalysts. These catalysts have relatively high turnover frequencies and they can work in a wide pH range for many hours of operation.